Pinene-rich essential oils from Haplophyllum dauricum (L.) G. Don display anti-insect activity on two stored-product insects. (May 2019) - Cao, Ju-qin; Pang, Xue; Guo, Shan-shan; Wang, Yang; Geng, Zhu-feng; Sang, Yu-li; Guo, Peng-ju; Du, Shu-shan
Abstract: Continuous use of synthetic insecticides increases environmental contamination and resistance in many species. Botanical insecticides, such as essential oil, were considered to be suitable alternatives due to multiple modes of action and low mammalian toxicity. Haplophyllum dauricum is a overlooked plant for the control of stored-product insects. Five essential oils (EOs) from Haplophyllum dauricum collected in October and November, rich in pinene, were extracted and evaluated on anti-insect activity against two stored-product insects, Tribolium castaneum (Coleoptera: Tenebrionidae) and Lasioderma serricorne (Coleoptera: Anobiidae). The lethal doses (LD50 and LD90 ), lethal concentrations (LC50 and LC90 ) and percentage repellency (PR) were evaluated. The GC-MS analysis showed that pinene ( α -pinene and β -pinene) were major constituent of the EOs (54.61% and 57.33% in fruits, 46.80% in stems + leaves, and 30.57% in leaves), followed by β -phellandrene (14.49% and 21.34% in fruits and leaves), 3-carene (26.84% in leaves) and limonene (15.77%, 11.09%, 12.40%, 7.59%, and 6.24% in five EOs, respectively). Five EOs and selected major compounds provided promising fumigant, contact and repellent activity against T. castaneum and L. serricorne . The EO of stems + leaves collected in October showed the strongest contact toxicity on T. castaneum (LD50  = 20.21μg/adult), as well as fumigant and contact toxicity on L. serricorne (LC50  = 17.17 mg/L air, LD50  = 25.46 μg/adult). All the five EOs exhibited effective repellent activity (PR>80%) against T. castaneum . The results highlight that the EOs from H. dauricum have a promising potential as eco-friendly botanical insecticides. Highlights: The compositions of five essential oils from different parts of Haplophyllum dauricum (L.) G. Don collected in different time were analyzed. Insecticidal and repellent activities of the five EOs and selected major compounds were evaluated to be effective on the control of Tribolium castaneum and Lasioderma serricorne . Essential oils from different parts of Haplophyllum dauricum and its major compounds have potential for development of natural insecticides and repellents on pest control.